2014
DOI: 10.1002/2013ja019552
|View full text |Cite
|
Sign up to set email alerts
|

On the solar cycle variation of the winter anomaly

Abstract: Constellation Observing System for Meteorology, Ionosphere and Climate, Ionosonde, and Global Ultraviolet Imager data have been used to investigate the solar cycle changes in the winter anomaly (the winter anomaly is defined as the enhancement of the F 2 peak electron density in the winter hemisphere over that in the summer hemisphere) in the last solar cycle. There is no winter anomaly in solar minimum, and an enhancement of about 50% in winter over summer ones on the same day of the year at solar maximum. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 46 publications
(71 reference statements)
2
57
0
Order By: Relevance
“…This indicates that, in 2006, the ionospheric winter anomaly did not exist at an altitude of ~680 km for low solar activity. It agrees with the results of Liu et al [] based on DMSP measurements at ~840 km and is also consistent with the result of Burns et al [], who reported that winter anomaly was not seen in the COSMIC data for solar minimum conditions. On the other hand, the global averaged Ne in DS was evidently larger than that in JS.…”
Section: Resultssupporting
confidence: 93%
“…This indicates that, in 2006, the ionospheric winter anomaly did not exist at an altitude of ~680 km for low solar activity. It agrees with the results of Liu et al [] based on DMSP measurements at ~840 km and is also consistent with the result of Burns et al [], who reported that winter anomaly was not seen in the COSMIC data for solar minimum conditions. On the other hand, the global averaged Ne in DS was evidently larger than that in JS.…”
Section: Resultssupporting
confidence: 93%
“…This phenomenon did not occur in June. The smaller winter crests in June might be related to the absence or weakness of winter anomaly in southern winter [ Torr and Torr , ; Burns et al ., ]. Overall, in the late afternoon hours, the dependence of hemispheric asymmetry of EIA on solar cycle is mainly associated with the weaker crests in local winter due to the weakness or absence of the vertical drifts in the solar minimum [ Scherliess and Fejer , ], as well as winter anomaly in the northern winter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we support the belief that the thermospheric wind is one of the most important components of the MSNA Thampi et al 2009). The winter anomaly in the F2 region is defined as the condition in which a greater daytime electron density is seen at the F2 peak in winter than in summer (Burns et al 2014;Rishbeth and Garriot 1969). This anomaly is primarily due to greater winter to summer differences of [O]/[N2] at solar maximum than at solar minimum for daytime hours.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, only 2001 data were used because the HMW07 does not change with solar cycle (Hagan 1993;Burns et al 2014).…”
Section: From the Hwm07 Modelmentioning
confidence: 99%
See 1 more Smart Citation